Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/biomedicines10092209
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery Care versus Traditional Care after Surgery in Pediatric Patients with Inflammatory Bowel Disease: A Retrospective Case-Control Study

Abstract: This study reports the outcomes of an enhanced recovery after surgery (ERAS) protocol in pediatric inflammatory bowel disease (IBD) surgery. Children who underwent surgery for IBD at two academic referral centers from January 2016 to June 2021 were included. Preoperative counseling, early enteral feeding (Impact®, Nestlé Health Science, and early mobilization were all part of the ERAS protocol. The outcomes (timing of first defecation, postoperative complications, and length of hospital stay (LOS)) were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Huguet et al indicated that the subcutaneous formulation of Infliximab (CT-P13) achieved higher drug levels, less immunogenicity, better perianal disease control, and improved mucosal healing compared to intravenous Infliximab [ 9 ]. Dipasquale and colleagues demonstrated that the enhanced recovery after surgery (ERAS) protocol significantly reduced postoperative complication rates and the timing of first defecation compared to traditional perioperative regimens, suggesting its superiority [ 10 ]. Finally, Papa et al investigated the impact of SARS-CoV-2 infection on the course of IBDs in patients treated with biological agents, revealing that SARS-CoV-2 infection did not increase IBD recurrence rates in this patient cohort [ 11 ].…”
mentioning
confidence: 99%
“…Huguet et al indicated that the subcutaneous formulation of Infliximab (CT-P13) achieved higher drug levels, less immunogenicity, better perianal disease control, and improved mucosal healing compared to intravenous Infliximab [ 9 ]. Dipasquale and colleagues demonstrated that the enhanced recovery after surgery (ERAS) protocol significantly reduced postoperative complication rates and the timing of first defecation compared to traditional perioperative regimens, suggesting its superiority [ 10 ]. Finally, Papa et al investigated the impact of SARS-CoV-2 infection on the course of IBDs in patients treated with biological agents, revealing that SARS-CoV-2 infection did not increase IBD recurrence rates in this patient cohort [ 11 ].…”
mentioning
confidence: 99%